Analisis Penerapan Etika Bisnis Islam Dalam Keberhasilan Usaha : Studi Pada Usaha Rempeyek Ilham Kota Jambi - Andriani, Beid Fitrianova; A. Tarmizi; Putri E., Aurelia Zahwa (Lembaga Pengembangan Kinerja Dosen, 2023)
This thesis is entitled Analysis of the Application of Islamic Business Ethics in Business Success (Study on Ilham's rempeyek business in Jambi City). This study aims to determine the application of Islamic business ethics in accordance with the principles of Islamic business ethics according to Faisal Badroen and the indicators of business success are capital, income, sales volume, production output and labor. The method used in this research is descriptive qualitative, where in collecting data the researcher uses observation, interview and documentation methods. The results showed that Ilham's peanut brittle business had implemented Islamic business ethics well in running his business and had a positive impact on the success of his business. Obstacles in applying Islamic business ethics to Ilham's peanut brittle business in Jambi city are keeping promises caused by a lack of manpower in the production sector causing delays in product delivery to consumers and inaccuracy in delivering products to consumers. The solution in applying Islamic business ethics to Ilham's peanut brittle business in the city of Jambi is to recruit workers, especially in the production sector so that production results can meet consumer demands and be more careful and thorough when delivering products to consumers.